Enhancing CaP Biomimetic Growth on TiO2 Cuboids Nanoparticles via Highly Reactive Facets - Ruso, Juan M. (2013)
Pure decahedral anatase TiO2 particles with high content of reactive {001} facets were obtained from titanium(IV) tetrachloride (TiCl4) using a microemulsions droplet system at specific conditions as chemical microreactor. The product was systematically characterized by X-ray diffraction, field-emission scanning and transmission electron microscopy (FE-SEM, TEM), N2 adsorption-desorption isotherms, FT-IR and UV-vis spectroscopy, and photoluminescence studies. The obtained cuboids around 90 nm in size have a uniform and dense surface morphology with a BET specific surface area of 11.91 m(2) g(-1) and a band gap energy (3.18 eV) slightly inferior to the anatase dominated by the less-reactive {101} surface (3.20 eV). The presence of reactive facets on titania anatase favors the biomimetic growth of amorphous tricalcium phosphate after the first day of immersion in simulated human plasma. The results presented here can facilitate and improve the integration of anchored implants and enhance the biological responses to the soft tissues.